2019
DOI: 10.1136/archdischild-2018-316539
|View full text |Cite
|
Sign up to set email alerts
|

Improved care and survival in severe malnutrition through eLearning

Abstract: BackgroundScaling up improved management of severe acute malnutrition (SAM) has been identified as the nutrition intervention with the greatest potential to reduce child mortality but it requires improved operational capacity.ObjectiveTo investigate whether an eLearning course, which can be used at scale in resource-poor countries, leads to improved diagnosis, clinical management and survival of children with SAM.DesignA 2-year preintervention and postintervention study between January 2015 and February 2017.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We have previously demonstrated that the malnutrition eLearning course improved knowledge, understanding and skills of health professionals in the diagnosis and management of children with SAM, leading to changes in clinical practice and improved confidence, and improved identification of SAM and almost all aspects of the WHO 'Ten Steps' of casemanagement, and reduced case-fatality [32,33]. This study further demonstrates that scaling up capacity/ training in malnutrition management, a recognised challenge in most LMICs [22][23][24][25][26], is possible through eLearning if it is supported by contextually appropriate delivery and implemented as part of curriculum development or in-service training.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that the malnutrition eLearning course improved knowledge, understanding and skills of health professionals in the diagnosis and management of children with SAM, leading to changes in clinical practice and improved confidence, and improved identification of SAM and almost all aspects of the WHO 'Ten Steps' of casemanagement, and reduced case-fatality [32,33]. This study further demonstrates that scaling up capacity/ training in malnutrition management, a recognised challenge in most LMICs [22][23][24][25][26], is possible through eLearning if it is supported by contextually appropriate delivery and implemented as part of curriculum development or in-service training.…”
Section: Discussionmentioning
confidence: 99%
“…The malnutrition eLearning evaluation (MeLE) was a prospective, longitudinal, cross-country, interrupted time-series study that took place in Ghana, Guatemala, El Salvador and Colombia. The outcomes and impact of the malnutrition eLearning course on knowledge gain, changes in practice and clinical outcomes were measured and details of the methods and findings have been published [32,33]. As part of the study, we devised, implemented and evaluated different delivery models to overcome contextual IT infrastructure challenges in Ghana.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations